Prosaccade and Antisaccade Behavior in Fragile X‐Associated Tremor/Ataxia Syndrome Progression. Issue 4 (28th April 2022) - McLennan, Yingratana A.; Mosconi, Matthew W.; McKenzie, Forrest J.; Famula, Jessica; Krawchuk, Bennet; Kim, Kyoungmi; Clark, Courtney J.; Hessl, David; Rivera, Susan M.; Simon, Tony J.; Tassone, Flora; Hagerman, Randi J.
ABSTRACT: Background: Quantitative measurement of eye movements can reveal subtle progression in neurodegenerative diseases. Objective: To determine if quantitative measurements of eye movements may reveal subtle progression of fragile X‐associated tremor and ataxia (FXTAS). Methods: Prosaccade (PS) and antisaccade (AS) behavior was analyzed in 25 controls, 57 non‐FXTAS carriers, and 46 carriers with FXTAS. Results: Symptomatic individuals with FXTAS had longer AS latencies, increased rates of AS errors, and increased AS dysmetria relative to non‐FXTAS carriers and controls. These deficits, along with PS latency and velocity, were greater in advanced FXTAS stages. Conclusion: AS deficits differentiated FXTAS from non‐FXTAS premutation carriers implicating top‐down control and frontostriatal deterioration. However, the absence of group differences between non‐FXTAS carriers and controls in AS and PS markers suggests saccade performance may not be a sensitive enough measure for detecting conversion to FXTAS, but instead more helpful as translational biomarkers of FXTAS progression.